Meeting and open session of the World Meteorological Organization’s The Polar Prediction Project’s (PPP) Societal and Economic Research and Applications (SERA) task team: Travelling to Antarctica: A conversation on Antarctic environmental forecasting services to improve the safety of operational, touristic and research activities - Carrasco Cerda, Jorge Fernando; Uribe, Paola (My University, 2019)
(8-12 April 2019, Punta Arenas, Chile)The Polar Prediction Project’s (PPP) Societal and Economic Research and Applications (SERA) task team addresses the social-science and economics aspects of the...
Keywords: None